The Presence of CPM (Asia) in the Indonesian MSMEs: A Qualitative Study for Firm, Macroeconomic, Market vs MSME Growth - DC Ethan Samuel; Irma M Nawangwulan; Samuel PD Anantadjaya; Timotius A Rachmat; Brian McNerney; Daniella CE Samuel; Karen McNerney (Journal of Sustainable Community Development (JSCD), 2026)
Micro, Small, and Medium Enterprises (MSMEs) account for more than 60 percent of national GDP in Indonesia and employ the highest number of workers, yet these enterprises still face fundamental barriers for growth. Limited marketing knowledge, fragmented distribution channels, and no consumer insight system have made it impossible for MSMEs to compete with large companies and to enter the modern retail ecosystem. This condition indicates the opportunity for MSMEs to find external partners to get professionalized marketing solutions, modernized sales, and retail mechanisms that make it possible for them to grow sustainably. The degree of CPM (Asia) is a region-leading outsourced sales and marketing merchandising service and hence provides a strategic model for filling those gaps. By deploying field salesforces, implementing standardized merchandising practices, and leveraging data-driven consumer insights, CPM (Asia) ensures that enterprises can strengthen market visibility and consumer engagement. Such collaboration provides a path for Indonesian MSMEs to enhance their competitiveness without incurring the huge cost of building internal sales and marketing infrastructures. Additionally, the regional presence of CPM (Asia) will enable the transfer of best practices from the other Asian markets-particularly in terms of digital retail activation and omnichannel strategies-to Indonesia's evolving business landscape. Integration of the capabilities of CPM (Asia) and MSME development agendas will have firm-level and macroeconomic outcomes. At the enterprise level, MSMEs are enabled to have increased market accessibility, professionalized brand execution systems, and adaptive strategies to meet consumer demand. At the national level, such partnerships add value to Indonesia's policy priorities of inclusive growth, digital transformation (Bahtiar et al., 2025), and employment creation. The case of CPM (Asia) strongly advocates outsourcing not only as an efficiency mechanism but also as a strategic driver of innovation and competitiveness in emerging markets. CPM (Asia), in conclusion, is a good strategic partner to empower Indonesian MSMEs to overcome barriers to growth, harmonize with modern supply chains, and secure sustainable performance in the highly competitive regional economy.